Analysis of learning outcomes in engineering programs - Niño Rondón , Carlos Vicente; Medina Delgado, Byron; Castro Casadiego, Sergio Alexander; Puerto López, Karla Cecilia; Lozano Cardenas, Felix Joaquin (Ingeniería Solidaria, 2023)
Introduction: The present review article is the product of the research “Teaching digital modulation techniques in engineering: experiential learning theory “ developed at the Franciso de Paula Santander University and Pontificia Universidad Javeriana in 2022. Problem: The learning outcomes correspond to the statements related to what the future engineer is expected to be able to do, learn, understand and demonstrate. Objective: Analyze learning outcomes in engineering programs globally. Methodology: A methodology based on analysis stages is used for information selection through search filters and inclusion and exclusion criteria, design for the classification of information by geographic location and area of knowledge, with qualitative results by location and trends by area of knowledge. Results: Divergence was observed towards the way in which learning outcomes are evaluated, and convergence towards the need to involve agents external to the academy in the feedback for the learning outcomes evaluation processes. Conclusion: This allows for the identification of individual and collective strengths and weaknesses, which helps to make informed decisions to improve the quality of education. Originality: Originality is based on the way in which the information is analyzed, considering information by areas of knowledge as well as by continents. Limitations: None given the nature of the literature review.